Structural based study to identify new potential inhibitors for dual specificity tyrosine-phosphorylation- regulated kinase. (October 2020) - Bhardwaj, Vijay Kumar; Singh, Rahul; Sharma, Jatin; Das, Pralay; Purohit, Rituraj
Highlights: Potential Pyrrolone-fused benzosuberene (PBS) molecules reported for targeting human DYRK1A receptor. Computational molecular docking and MMPBSA studies showed that new molecules have better binding affinity compared to previously reported co-crystallized molecule. Reported molecules show a novel binding mechanism, with more binding affinity and binding free energy towards receptor protein could be used as a lead for developing inhibitors for human DYRK1A. Abstract: Background and Objectives The Dual-specificity tyrosine-phosphorylation regulated kinase-1A (DYRK1A) a serine/threonine kinase that has freshly gained recognition as an essential drug target due to the discovery of its involvement in pathological diseases. The development of new potent inhibitors of DYRK1A would contribute to clarify the molecular mechanisms of associated diseases. It would administer a new lead compound for molecular-targeted protein, which was the primary focus of our study. Methods The library of in-house synthesized pyrrolone-fused benzosuberene (PBS) compounds was docked with DYRK1A receptor. Further, molecular mechanics-Poisson Boltzmann surface area (MM-PBSA) estimations were conducted to confirm our docking outcomes and compared the stability of chosen complexes with the 2C3 (standard molecule) complex. Results This study reports Ligand15, Ligand14, and Ligand11 as potent inhibitors which showed higher ligand efficiency, binding affinity, lipophilic ligand efficiency, and favorable torsion values as compared to 2C3. Conclusion The stated methodologies revealed a unique mechanism of active site binding. The binding interactions within the active site showed that the chosen molecules had notable interactions than the standard molecule, which led to the generation of potential compounds to inhibit DYRK1A. Graphical abstract: Image, graphical abstract